A survey of rate of victimization and attitudes towards physical violence among school-aged children in Turkey - Deveci, S. E.; Acik, Y.; Ayar, A. (Wiley, 2008)
Background Violence of any type is a serious issue in the lives of many children from all racial, cultural and economic backgrounds, and is a topic of enormous societal concern in any society. The purpose of this study was to examine the rate of exposure to violence as victims, and attitudes towards physical violence among school-aged children in eastern Turkey. Methods All the basic education schools in Elazig, a typical eastern Anatolian city, were included. A total of 3725 fifth and sixth graders were asked to answer survey questions about the rate of physical violence exposure in their everyday lives and whether they thought the violence was an 'acceptable' behaviour. Results The mean age of participants was 12.8 years with 46.8% boys and 53.2% girls, and their socio-economic status ranged from low-income to upper middle class. Seventy-four per cent of school-aged children reported exposure to at least one case of physical violence in their lives, and 43.4% reported experiencing physical violence within previous 12 months. Higher rates of exposure to physical violence were reported by boys than girls (P= 0.0001). Of the victims, 33.8% regarded physical violence as an acceptable or inevitable way of solution or responding to life events. Conclusions Results from the self-report of the receiving end of violent behaviours indicate that physical violent victimization is at an alarmingly high rate among children of eastern Turkey, and a significant per cent of these victims approves violence as a way of solution.
Keywords: child abuse; children; physical violence; Turkey